پاكتاوی ڕه‌گه‌زی كورد له‌ باكوری كوردستان 1919- 1929 - ئاغجه‌له‌ری, حمه‌ تاهیر; مەجید, ئارام علی (Sulaimani Journal for Humanities, 2023)
The genocide of the Kurds in North Kurdistan during the years (1919-1929) is a sensitive and eventful period in the policy of erasing the Kurdish race on the levels (physical, economic, cultural and biological, etc.) by Kemalist Turkey the first theme focuses on the ethnic cleansing in the period (1919-1924) and the second theme on the period between (1924-1929) The Kurdish ethnic genocide is discussed, and the at the results are presented.